Trajectory control for tire burst vehicle using the standalone and roll interconnected active suspensions with safety-comfort control strategy. (August 2020) - Sathishkumar, P.; Wang, Ruochen; Yang, Lin; Thiyagarajan, J.
Highlights: Suspension approach to control trajectory of tire burst vehicle was proposed. Priority based comfort-safety MPC was used for controlling HCV. HPIS and standalone coordinated control systems enhanced safety and comfort. It is convenient to abandon the passive suspension with ARB for safety. Abstract: The lateral pulling of tire burst vehicle results in accident and fatality on the highway due to its sudden C.G displacement of the vehicle. Improper steering input leads to detach wheel from vehicle and rollover accident due to the weight transfer towards the flat tire. Therefore, this paper attempts to reduce the lateral velocity and its displacement of the vehicle by producing the force through suspension actuator within the suspension limitation and without affecting the steering characteristics. For the analysis, 4-axle truck with velocity controller and steering system incorporated model was built in AMESim environment, which is exported into Matlab/Simulink for the co-simulation. Hydraulic control valve integrated standalone and roll interconnected active suspension scheme's state space model was identified in Matlab through simple identification method for the comfort and safety MPC controller design. Finally, the results of passive system with Anti-roll bar (ARB) and without ARB, passive and active roll interconnected suspensions, comfort and coordinated control standalone active suspension system are comprised to illustrate the effectiveness and its control strategy. In addition, this work showcased the motion trajectory of vehicle with a flat tire on running over highway with and without steer maneuver.